The Effect of Local Metakaolin Developed from Natural Material Soorh on Selected Properties of Concrete/Mortar - Keerio, M.A. (Springer Science and Business Media B.V., 2022)
In this research study the effect local metakaolin produced from natural material Soorh of Thatta, District of Sindh, Pakistan on compressive strength of mortar/concrete, permeability, corrosion potential and carbonation depth of concrete, alkali silica reaction (ASR) and sulphate attack of mortar is investigated. However, the natural material Soorh is calcined by an electric furnace at 800Â Â°C for 2Â h duration to produce metakaolin. Moreover, two mixes of mortar/concrete without accumulation of developed metakaolin were made and ten mixes of mortar/concrete were prepared where cement is replaced by developed metakaolin as 5 to 25, with 5 increment, by weight of cement. It was concluded upon the results of this research that the utilization of 15 metakaolin as cementitious ingredient has significantly improvement in properties of mortar/concrete. Â© 2021, Springer Nature B.V.